Loss of species and functions in a deforested megadiverse tropical forest - Lisieux Fuzessy; Sandrine Pavoine; Laura Cardador; Joan Maspons; Daniel Sol (Conservation Biology, 2024)
Tropical species richness is threatened by habitat degradation associated with land‐use conversion, yet the consequences for functional diversity remain little understood. Progress has been hindered by difficulties in obtaining comprehensive species‐level trait information to characterize entire assemblages and insufficient appreciation that increasing land‐cover heterogeneity potentially compensates for species loss. We examined the impacts of tropical deforestation associated with land‐use heterogeneity on bird species richness, functional redundancy, functional diversity, and associated components (i.e., alpha diversity, species dissimilarity, and interaction strength of the relationship between abundance and functional dissimilarity). We analyzed over 200 georeferenced bird assemblages in the Atlantic Forest of Brazil. We characterized the functional role of the species of each assemblage and modeled biodiversity metrics as a function of forest cover and land‐cover heterogeneity. Replacement of native Atlantic Forest with a mosaic of land uses (e.g., agriculture, pastures, and urbanization) reduced bird species richness in a nonrandom way. Core forest species, or species considered sensitive to edges, tended to be absent in communities in heterogenous environments. Overall, functional diversity and functional redundancy of bird species were not affected by forest loss. However, birds in highly heterogenous habitats were functionally distinct from birds in forest, suggesting a shift in community composition toward mosaic‐exclusive species led by land‐cover heterogeneity. Threatened species of the Atlantic Forest did not seem to tolerate degraded and heterogeneous environments; they remained primarily in areas with large forest tracts. Our results shed light on the complex effects of native forest transformation to mosaics of anthropogenic landscapes and emphasize the importance of considering the effects of deforestation and land‐use heterogeneity when assessing deforestation effects on Neotropical biodiversity.